Comparison between sentinel lymph node hybrid scintigraphy and blue dye technique in breast cancer patients: An institutional experience - Siddique, Maimoona; Hassan, Aamna; Nawaz, Muhammad; Bashir, Humayun; Chaudhry, Muhammad (World Journal of Nuclear Medicine, 2020)
To compare the detection efficacy of radionuclide lymphoscintigraphy (LS) versus patent blue dye (PBD) technique for hidden sentinel lymph node (SLN) in breast cancer patients and to determine which modality is better for SLN detection. One hundred and thirty-four early stage breast cancer female patients with clinically negative axilla who underwent post technetium-99m nanocolloid injection single photon emission computed tomography (SPECT-CT) for negative SLN on planar imaging were studied prospectively between 2015 and 2017. Following SPECT-CT, patients underwent peroperative gamma probe count detection GP-CD and PBD technique. Visually, blue stained ± hot nodes were surgically removed and subjected to histopathological analysis. The detection rate by individual method was calculated. Kappa statistics were applied to calculate overall agreement between radioisotope and PBD techniques for diagnostic value assessment. One hundred and thirty-four patients underwent SPECT-CT LS and PBD injection. Mean age: 47 ± 7.6 years (range: 26–82 years). Forty-nine (36.6%) had T1 and 85 (63.4%) T2. SPECT-CT LS detected SLN in 105/134 cases (success rate: 78.4%), later GP-CD localized “hot nodes”in additional 20 cases (success rate: 93.3%). The PBD successfully localized SLN in 131/134 (97.8%) cases. Three cases remained negative on both radioisotope and PBD localization, which on subsequent nodal dissection had metastatic disease. All SLNs detected on SPECT-CT showed blue dye uptake. In 112 cases, more than one SLN was surgically removed. Frozen section analysis of excised SLNs showed metastasis in 31%. Overall moderate agreement (k = 0.56) was calculated. No statistically significant difference was seen between isotope detection and PBD. Radionuclide sentinel mapping has good detection rate particularly combined with peroperative GP-CD. The PBD has added value to reduce false-negative rate of SLN mapping and can substitute radionuclide imaging with negative results.
Keywords: Breast cancer; patent blue dye; sentinel lymph node; single photon emission computed tomography sentinel lymphoscintigraphy